ANALYSIS OF THE INCOME OF CARROT TRADERS AT PASAR BARU KEFAMENANU - Dominggus Wilfridus Amfotis; Maria Bano; Paulus Un; Damianus Adar (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aims to determine the income and business feasibility of carrot traders at Pasar Baru Kefamenanu, North Central Timor Regency, East Nusa Tenggara Province. Carrots are a horticultural commodity that is quite popular with the public. As a transaction center, Pasar Baru Kefamenanu plays an important role in the distribution and trade of carrots. However, information regarding the income and business feasibility of carrot traders is still limited. This study used a quantitative descriptive approach with a sample of 30 traders randomly selected from 120 active traders. Data were collected through observation, interviews, and questionnaires, then analyzed by calculating costs, revenues, income, and business feasibility using Break Even Point (BEP) analysis and the Revenue/Cost (R/C) ratio. The results showed that most carrot traders were of productive age, female, and had more than 10 years of trading experience. The average daily revenue of traders reached Rp 1,010,833 with a total cost of Rp 649,168, resulting in a net income of Rp 361,655 per day. The break-even point (BEP) analysis shows a production break-even point of 29.9 kg per day, while the average sales volume reaches 40.4 kg per day, indicating the business is above the break-even point. The BEP price of Rp 288,918 is lower than the average selling price. The R/C ratio of 1.55 indicates that the carrot trading business at Pasar Baru Kefamenanu is feasible and profitable for traders.